Sistem Informasi Akuntasi Ketetapan Pajak Di Kantor Pelayanan Pajak Pratama Jombang (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of writing the report is to determine the effect of the accounting information system on tax assessments at KPP Pratama Jombang Tebuireng. The estimation results obtained from the regression coefficient of the tax accounting information system (SIAP) variable of 0.025 which means that the SIAP variable has a positive and significant effect on tax assessment. This can be seen from the t-test which has a greater probability value than the 5% significance level.